KEBERADAAN KAPANG PENGKONTAMINASI BEBERAPA PRODUK JAMU SERBUK KEMASAN YANG BEREDAR DI - Halizah, Halizah; Fifendy, Mades; Nurmiati, Nurmiati (STKIP PGRI Sumbar, 2013)
ABSTRACTHealth is absolutely necessary effort, either individually or in groups. Integration efforts include health prevent, healing, restoration, and health improvement. Way that can be done to obtain that level optimal health one of with benefit medicine plant are packed in the form of herbal or traditional medicine. Herbal medicine is mixe of natural plant based ingredients that have not been processed. That material called simplisia may be whole plants or parts of plants such as leaves, flowers, fruit, seeds, bark, wood, rhizomes, roots or eksudat plant. Research has been conducted in order to determine the presence of mold contaminants on a powder packing of medicine products circulating in the city of Padang. The research was conducted in August and September 2013 in the Laboratory of Microbiology Department of Biology, State University of Andalas Padang. Sampling was conducted surveys herbs, herbs selected as 6 brand with 3 different production based on the brand most widely sold and often consumed by people in the city of Padang. Isolation is done using a Medium PDA with level of dilution 10-1 to 10-7. From this research, six types of mold included to the class Ascomycetes, Deuteromycetes, and Zygomycetes. Molds, namely Aspergillus sp.1, Aspergillus sp.2, Verticillium sp, Penicillium sp, Curvularia sp and Mucor sp. The conclusion of this research is that the herbal powder packing products circulating in the city of Padang contaminated by several types of mold.